A helping hand: roles for accessory cells in the sense of touch across species - Logan, David R.; Hall, Jesse; Bianchi, Laura (Frontiers in Cellular Neuroscience, 2024)
During touch, mechanical forces are converted into electrochemical signals by tactile organs made of neurons, accessory cells, and their shared extracellular spaces. Accessory cells, including Merkel cells, keratinocytes, lamellar cells, and glia, play an important role in the sensation of touch. In some cases, these cells are intrinsically mechanosensitive; however, other roles include the release of chemical messengers, the chemical modification of spaces that are shared with neurons, and the tuning of neural sensitivity by direct physical contact.Despite great progress in the last decade, the precise roles of these cells in the sense of touch remains unclear. Here we review the known and hypothesized contributions of several accessory cells to touch by incorporating research from multiple organisms including C. elegans, D. melanogaster, mammals, avian models, and plants. Several broad parallels are identified including the regulation of extracellular ions and the release of neuromodulators by accessory cells, as well as the emerging potential physical contact between accessory cells and sensory neurons via tethers. Our broader perspective incorporates the importance of accessory cells to the understanding of human touch and pain, as well as to animal touch and its molecular underpinnings, which are underrepresented among the animal welfare literature. A greater understanding of touch, which must include a role for accessory cells, is also relevant to emergent technical applications including prosthetics, virtual reality, and robotics.